Penerapan Metode Istihsan Pada Bidang Muâmalah Mâliyyah (Hukum Ekonomi Syariah) - Panji Adam (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Istihsan is one of the ijtihad methods disputed by the scholars ushul fiqh, although in reality, all scholars use it practically. The establishment of the law by istihsan method is widely carried out by scholars among the Hanafiyyah and Malikiyyah so that in the history of ushul fiqh, the Hanafiyyah are known as the group that uses istihsan as one of the methods of istinbâth al-ahkâm (determination of the law). Imam Shafi'i is a cleric who rejects istihsan as a method of determining Islamic law. But in practice Imam Shafi'i also uses istihsan as a method of determining Islamic law. The science of ushul fikih has a significant role in contributing to the existence of Islamic law, especially in the field of Sharia economic law. Research method conducted based on normative juridical approach, The specification of research used is analytical descriptive, The type of data used in this research, namely secondary data, data collection method used is literature study and analysis of secondary data that is qualitative. The results showed that istihsan is one of the methods of istinbâth al-ahkâm, which can be used as an argument and a proof of syara' and serves in determining the validity of an agreement / transaction in the field of Sharia economic law.